1998
DOI: 10.1038/1770
|View full text |Cite|
|
Sign up to set email alerts
|

Assignment of Tangier disease to chromosome 9q31 by a graphical linkage exclusion strategy

Abstract: A low level of high density lipoprotein (HDL) cholesterol is a strong predictor of ischaemic heart disease (IHD) and myocardial infarction. One cause of low HDL-cholesterol is Tangier disease (TD), an autosomal codominant inherited condition first described in 1961 in two siblings on Tangier Island in the United States of America. Apart from low HDL-cholesterol levels and an increased incidence of atherosclerosis, TD is characterized by reduced total cholesterol, raised triglycerides, peripheral neuropathy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 20 publications
1
33
0
1
Order By: Relevance
“…Complementary sources of data were used to evaluate the genes underexpressed in the Tangier cells. In 1998, a genetic linkage strategy was used to assign the TD gene to an approximately 7-cM region of human chromosome 9q31 (21). Public database inspection revealed few named genes in this region.…”
Section: Resultsmentioning
confidence: 99%
“…Complementary sources of data were used to evaluate the genes underexpressed in the Tangier cells. In 1998, a genetic linkage strategy was used to assign the TD gene to an approximately 7-cM region of human chromosome 9q31 (21). Public database inspection revealed few named genes in this region.…”
Section: Resultsmentioning
confidence: 99%
“…However, it can only provide an initial localization of susceptibility genes and requires subsequent extensive fi ne-mapping studies. This approach has been successful in localizing the causative genes in rare monogenic disorders, such as Tangier disease ( 86 ), but it has been less benefi cial for common (i.e., complex) polygenic conditions. A large number of genome-wide linkage screens for continuous and dichotomous HDL-C and related traits (such as apoAI and apoAII levels) have been performed in FHA as well as nonascertained family samples from different populations [reviewed by (87)(88)(89)(90)].…”
Section: Single Gene Defects Associated With High Hdl-c Levelsmentioning
confidence: 99%
“…Initial studies to elucidate the genetic defect in Tangier disease, using positional cloning, mapped the defective gene to a region on chromosome 9 (17). In a recent report, we (18) and others (48,49) have identified that mutations in the ABC1 gene are the molecular defect in Tangier disease.…”
mentioning
confidence: 99%